THE IMPACT OF COMMUNITY PARTICIPATION IN VILLAGE FUND MANAGEMENT ON FRAUD PREVENTION - Endang Tri Pratiwi; Haliah Haliah; Nirwana Nirwana; Andi Kusumawati (JIAR : Journal Of International Accounting Research, 2024)
This study aims to analyze the impact of community participation in village fund management on fraud prevention. This study uses a qualitative approach with a case study method in Kolowa Village, Central Buton Regency. The research informants consisted of various elements of society, including village officials, members of the Village Consultative Body (BPD), and the general public involved in the management of village funds. Data collection was carried out using several techniques, namely interviews, observations, and documentation studies and then thematic analysis was carried out. In addition, data triangulation will also be carried out to ensure the accuracy and consistency of information obtained from various sources. The results of the study found that community participation in the management of village funds has an impact on fraud prevention. Through active community involvement, transparency and accountability in the management of village funds can be improved, thereby minimizing the possibility of fraud. In addition, community participation also contributes to improving the competence of human resources in village fund management.